Shale Gas Potential In Jambi Sub-Basin, Indonesia: Insights From Geochemical and Geomechanical Studies - Reddy Setyawan; Edy Ariyono Subroto; Benyamin Sapiie; Randy Condronegoro; Beiruny Syam (UIR PRESS, 2020)
Jambi sub-basin, which is located in South Sumatra, Indonesia has enormous potential of shale gas play. Yet, detailed geological studies are rarely undertaken to understand this relatively new hydrocarbon play concept. This paper presents a combination of geochemical and geomechanical studies with the aim to better understand: (1) the maturity level of source rock; (2) the mechanical properties of shale; and (3) the quality of hydrocarbon source rock. This research began with determination of wells that penetrate the Talangakar and Gumai Formations that have shale in it. Source rock analysis was done by using TOC (total organic carbon), S1, S2, S3, Tmax, and Ro (vitrinite reflectance) data. Geomechanical evaluation was done by using XRD and well logs data. Brittleness index was obtained by using Jarvie et al. (2007) formula, based on the XRD data. S-wave and P-wave are used to calculate the rock strength, Young's modulus and Poisson's ratio with UCS-To methods.Source rock in the Geragai belongs to the of moderate-to-good category because it has more than 0.5% TOC and potentially forms gas because it has a type III kerogen. JTBS-2 well is the only well in the Geragai area which already mature and has been able to produce hydrocarbons, because it passed the oil and gas windows. Source rock in the Betara belongs to moderate-to-good category because it has more than 0.5% TOC potentially forms gas because it has a type III kerogen. Most formations in the Betara are not yet mature based on the value of Ro and Tmax. In wells that have not reached the oil window nor gas windows, the prediction line drawn on the Petroleum Source Rock Summary chart, estimated that they would pass the gas window at Lower Talangakar Formation or Lahat Formation at depth of more than 8000 feet. The results of XRD analysis showed that the Betara had a high brittleness index with an average of 0.809. Talangakar Formation has a higher rock strength values than Gumai Formation, both in Betara high and Geragai deep. The principle that say the rocks which have high TOC values will have a high value of BI can be proven in the study area, the rocks that have high Ro will have a high value of BI, cannot be identified in the study area. With sufficient high value of rock strength and low abundance of clay minerals, the rocks at Talangakar Formation is good for hydraulic stimulation.